Mapping Real Estate Purchase Intention Research in Developing Countries: A Decade of Bibliometric Evidence (2015–2025) - Salsabil, Syifa Hanifa; Windarko, Windarko; Aulia, Nasywa Shafa; Kusumawardhani, Arum (West Science Interdisciplinary Studies, 2025)
The increasing complexity of housing markets in developing countries, driven by economic, geographic, social, and cultural dynamics, calls for a comprehensive understanding of factors influencing real estate purchase intention. This study conducts a bibliometric analysis of 171 Scopus-indexed articles published between 2015 and 2025, aiming to map the intellectual landscape and identify research patterns in this domain. Using tools such as Scopus Analyze, VOSviewer, and Biblioshiny, the study examines publication trends, influential works, thematic clusters, and international co-authorship networks. Findings highlight the dominance of the Theory of Planned Behavior (TPB) in explaining consumer decisions, with purchase intention, attitude, and perceived behavioral control emerging as core constructs. Key thematic clusters include sustainability, housing policy, digital integration in decision-making, and cultural perceptions. Despite growing attention to green housing and environmental sustainability, topics such as feng shui and ethnocentrism remain underexplored. The study contributes to a deeper conceptual and methodological understanding of consumer behavior in housing markets and offers direction for future interdisciplinary research focused on inclusive and sustainable housing development.